A New Face in a Familiar Place. Iceland in the Mackerel Negotiations, 2010-2014 - Ólafur Valdimar Ómarsson 1989- (2018)
This thesis examines the mackerel negotiations from 2010-2014 and the role that Iceland played in them, putting it into context with a theoretical approach to negotiations. The study is based on interviews with five people who participated in the negotiations from the Faroe Islands, Iceland, and Norway. The interviews focused on how the participants approached the negotiations and what they thought of the Icelandic approach. By comparing the results of the interviews with the established theoretical framework, a deeper understanding of the process of the mackerel negotiations can be gained. Iceland was brought into the negotiations after mackerel unexpectedly changed its migration pattern and moved into waters under Icelandic jurisdiction. Mackerel was a new fish stock for Iceland and brought with it the challenge of reaching a management agreement with the European Union, Faroe Islands, and Norway. That, along with unique relationships with each of the other three participants throughout the negotiations, made for interesting negotiations which ended with an agreement of which Iceland was not a party. Þessi rannsókn skoðar makrílviðræðurnar frá 2010-2014 og þátt Íslands í þeim og setur það í samhengi við fræðilega umfjöllun um samningaferli. Rannsóknin er byggð á fimm viðtölum við fólk sem tók þátt í viðræðunum fyrir hönd Færeyja, Íslands, og Noregs. Viðtölin einblíndu á hvernig þátttakendurnir nálguðust viðræðurnar sem og viðhorf þeirra til nálgun Íslands. Með því að bera saman niðurstöður viðtalanna við fræðilega umfjöllun um samningaferlið er hægt að öðlast dýpri skilning á því sem átti sér stað í makrílviðræðunum. Ísland fékk aðild að viðræðunum eftir að makríllinn óvænt breytti hegðun sinni og fór að koma í stórauknum mæli inn í íslenska lögsögu. Makríll var nýr fiskistofn fyrir Ísland og honum fylgdi sú áskorun að ná fiskveiðistjórnunarsamning við Evrópusambandið, Færeyjar, og Noreg. Ísland var vel kunnug slíkum samningum en var nýliði þegar kom að makríl. Ofan á það átti Ísland sérstakt samband við ...